Temporal meta-model framework for Enterprise Information Systems (EIS) development - Davis, Jon Edward (Curtin University, 2014)
This thesis has developed a Temporal Meta-Model Framework for semi-automated Enterprise System Development, which can help drastically reduce the time and cost to develop, deploy and maintain Enterprise Information Systems throughout their lifecycle. It proposes that the analysis and requirements gathering can also perform the bulk of the design phase, stored and available in a suitable model which would then be capable of automated execution with the availability of a set of specific runtime components.